The Study of Delivery Medicine Using ENDS Device: A Bromhexine Study Case - Cipto Kokadir; Ervina Kalinda; Kamarza Mulia (Eduvest - Journal of Universal Studies, 2026)
Electronic Nicotine Delivery Systems (ENDS) have been used over the last decade as substitutes for conventional cigarettes. The delivery of active pharmaceutical ingredients (APIs) using these devices has been reported in the literature; however, many puffs are required to achieve a therapeutic dose. This study aimed to deliver and measure bromhexine hydrochloride (BRM) as an API via inhalation using an e-liquid formulation. The e-liquid was obtained by trapping the aerosol and measuring the concentration using high-performance liquid chromatography–mass spectrometry (HPLC-MS) in multiple reaction monitoring (MRM) mode. Our study demonstrated that five puffs accumulated 3.3156 ng/mL of BRM, and the efficiency of the ENDS device was calculated to be 99.8%. In addition, computational simulations were performed, resulting in a binding affinity of BRM of −7.3 kcal mol⁻¹, compared with −8.1 kcal mol⁻¹ for salbutamol. Nevertheless, BRM formed a hydrogen bond between the amine group and Ser204, π-alkyl bonds with Ala200 and Val114, and alkyl interactions with Phe289 and Phe290. However, the BRM interaction with the protein did not form a stable complex in the dynamic simulation, although it may act as an allosteric modulator or partial agonist. The results of this study corroborate previous findings that ENDS technology may offer broad innovations for inhaled medicines.